THE INFLUENCE OF COMPETENCE AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE WITH COMMITMENT AS A MEDIATING VARIABLE - Ilwanti, Yulia; Asnawi, Meinarni; Adji, Sandra Sukmaning (Transpublika Publisher, 2024)
This research looks into the influence of competence and career development on employee performance with commitment as a mediating variable. The study utilises a quantitative approach with descriptive analysis. It collects primary and secondary data. The target group comprises all personnel in the administrative offices of Class I Mopah Merauke, Sorong and Wamena Airports, totalling 231 individuals. The research sample includes 140 individuals. The test results demonstrated that skills positively influenced staff performance and organisational commitment, while career development affected staff productivity and organisational commitment. Commitment was found to impact staff performance positively. However, skills and career development did not directly affect staff performance when mediated by organizational commitment.